A kind of low expansion coefficient transparent microcrystalline glass and preparation method thereof
By optimizing the composition and heat treatment process of the crystal crystal glass, low-expanded transparent crystal glass is prepared, which solves the problem of reduced transmittance of the crystal crystal glass in the prior art, and achieves high permeability, chemical stability and excellent mechanical properties.
Patent Information
- Application Number
- CN202211726325.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-12-30
AI Technical Summary
Under the influence of the heat treatment process, the transmittance of existing low-expanded crystalline glasses is easily reduced or even devitrified, which limits its use field and effect.
By optimizing the composition and heat treatment process of the crystal crystal glass, a transparent crystal crystal crystal glass with low expansion coefficient is prepared, which specifically includes adding an appropriate amount of SiO2, Al2O3, TiO2, ZrO2, Li2O, MgO, CeO2, SnO2 and other components to the glass, and adopting a stepped heat treatment process of nuclearization and crystallization treatment.
The high transmittance, chemical stability and excellent mechanical properties of low-expanded transparent microcrystalline glass are achieved. The expansion coefficient is adjustable within a certain range, the transmittance is greater than 88%, the microhardness is greater than 750HV, and the three-point bending strength is greater than 200MPa.
Smart Images

Figure BDA0004030145410000081 
Figure BDA0004030145410000091 
Figure BDA0004030145410000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microcrystalline glass production, and in particular to a low expansion coefficient transparent microcrystalline glass and a preparation method thereof. Background Art
[0002] Low expansion glass-ceramics mainly refers to Li 2 O、Al 2 O 3 、SiO 2 Glass with quartz as the main component is treated by strict heat treatment process to form glass-ceramics with β-quartz solid solution as the main crystal phase. The expansion coefficient of glass-ceramics can be adjusted arbitrarily within a certain range. Through the adjustment of heat treatment process, the glass-ceramics can also achieve zero expansion within a certain temperature range.
[0003] Through effective control of the composition and preparation process of glass-ceramics, an ultra-fine crystal structure is formed, and a nearly single-phase glass-ceramics is obtained, which has high transmittance in the visible light region. It has a high degree of crystallization, an ultra-fine microcrystalline structure, a uniform and dense texture, and excellent mechanical properties and wear resistance. Low-expansion transparent glass-ceramics has excellent electrical insulation, long-term dimensional stability and chemical stability due to its low alkali metal content and ordered microcrystalline structure. It has broad application prospects in the fields of chemical industry, electronics, navigation, exploration, and military.
[0004] However, for existing production technology, low expansion glass-ceramics is greatly affected by the heat treatment process during the actual crystallization process. Different heat treatment processes have a great impact on the transmittance of the glass. When the treatment temperature changes, the transmittance of the glass will be reduced, and the glass may even become devitrified, which seriously limits the application field and effect of low expansion glass-ceramics. Summary of the invention
[0005] The object of the present invention is to provide a low expansion coefficient transparent microcrystalline glass and a preparation method thereof, so as to solve the problem of reduced transmittance of microcrystalline glass after crystallization, obtain high transmittance low expansion transparent microcrystalline glass, reduce the expansion coefficient of glass, so that the glass has excellent mechanical properties and optical properties and chemical stability. To achieve the above purpose, the following technical solutions are adopted:
[0006] The technical solution of the present invention is achieved as follows: a low expansion coefficient transparent microcrystalline glass, the microcrystalline glass comprising the following components by mass percentage: 60%-75% SiO 2 、15%-28%Al 2 O 3 , 0.5%-2%TiO 2 , 2%-5% ZrO 2 , 2%-8%Li 2O, 0%-1% MgO, CeO 2 +SnO 2 +P 2 O 5 +Nd 2 O 3 + ZnO total 1%-4%, of which (TiO 2 +P 2 O 5 +ZrO 2 ) / Li 2 O is 0.3-1.2, (MgO+ZnO) / (SiO 2 +Al 2 O 3 )<0.02.
[0007] SiO 2 It is an essential component of the glass of the present invention and one of the main components of the crystal formed after heat treatment. 2 When the content of SiO is below 60%, the glass is prone to phase separation and has poor chemical stability. 2 If the content is above 75%, the melting temperature of the base glass will be too high, making clarification and homogenization difficult.
[0008] Al 2 O 3 It is an essential component for forming the glass network structure, which can improve the glass structure and chemical stability, refine the grains during heat treatment, and control the crystallization rate. In the present invention, if its content is less than 15%, it is not conducive to crystallization, it is difficult to control the crystallization rate, and the crystal size becomes larger. 2 O 3 When the content of exceeds 28%, melting of the glass becomes difficult, hindering the precipitation of target crystals.
[0009] Li 2 O is a necessary component for the formation of crystals. It can reduce the viscosity of the base glass and promote crystal formation. However, if its content is too low, it will be detrimental to the glass melting effect on the one hand, and it will be difficult to control the type of crystal precipitation on the other hand. 2 If the O content is too high, the chemical stability of the glass will deteriorate and it will be difficult to control during crystallization. Therefore, controlling the Li 2 O content in
[0010] Between 2%-8%.
[0011] ZrO 2 It is a necessary component in the present invention. First, it is used as a crystal nucleating agent to make the glass crystallize evenly, effectively control the precipitation of crystals, control the size of crystals, and avoid the influence of too large crystal size on optical properties; secondly, it improves the chemical stability of base glass and microcrystalline glass when the Li content is high. ZrO2 It can also effectively reduce the tendency of base glass to lose clarity during the forming process. 2 If the content is too high, the melting temperature of the glass will be increased, making it difficult to melt. In addition, the precipitation of the target crystalline phase will be inhibited during the crystallization process, making the crystallization uncontrollable. Therefore, in the present invention, the content of ZrO is controlled. 2 The content is between 2%-5%.
[0012] TiO 2 In the present invention, ZrO is an essential component. 2 Also used as a crystal nucleating agent, an appropriate amount of TiO 2 It can promote the crystallization of glass, make the glass crystallize evenly, improve the chemical stability of glass, and increase the ability to absorb ultraviolet rays. 2 Too high a content will increase the melting temperature of the glass, making it difficult to melt, and will also make the glass yellow-brown and reduce the permeability of the glass. Therefore, TiO 2 The content is between 0.5% and 2%.
[0013] P 2 O 5 It is an essential component of the composition of the present invention, which can effectively reduce the melting temperature of the base glass and increase the ZrO 2 The solubility of P is closely related to each other as composite nucleating agents. 2 O 5 , it is easy to cause phase separation of the base glass, and it is easy to lose transparency during the crystallization process, which seriously affects the optical properties of the microcrystalline glass. 2 O 5 The content is between 0.5%-1%.
[0014] In the present invention, the composite nucleus agent P is controlled 2 O 5 、ZrO 2 and TiO 2 Introduced in a certain proportion, it can affect the precipitation of glass-ceramics, especially Li 2 O is between 2% and 8%, which can make the base glass or glass-ceramics have a suitable thermal expansion coefficient, obtain a large crystal content and a suitable crystal size after crystallization, and improve the hardness and fracture toughness of the glass-ceramics. 2 O 5 、ZrO 2 and P 2 O 5 , and alkali metal oxides have a certain ratio relationship, in order to obtain high transmittance and low expansion microcrystalline glass with high transparency and mechanical properties. The preferred ratio of composite crystal nucleating agent to alkali metal oxide (TiO 2 +P2 O 5 +ZrO 2 ) / Li 2 O is between 0.3-1.2.
[0015] The introduction of MgO can improve the glass material properties to a certain extent, reduce the melting temperature, inhibit crystallization in the forming stage, refine the grains in the crystallization heat treatment stage and improve the optical properties of microcrystalline glass. If the content is too high, other crystal phases will be generated after crystallization, thereby affecting the mechanical properties and optical properties of the glass. In the present invention, the MgO content is controlled between 0% and 1%.
[0016] ZnO is an optional component in the present invention, and has a certain fluxing effect in the base glass, and helps to refine the grains during the crystallization process. The preferred lower limit is 1.0%. Too high a content will affect the optical properties of the glass after crystallization. Therefore, in the present invention, the ZnO content is controlled between 0% and 1%.
[0017] In the present invention, ZnO and MgO are optional components. Excessive content will increase the expansion coefficient of microcrystalline glass and affect the optical properties. In the present invention, the ratio of (MgO+ZnO) / (SiO 2 +Al 2 O 3 ) is less than 0.02,
[0018] The present invention does not contain K 2 O、Na 2 O, CaO, K 2 O、Na 2 O, as the outer body of the glass network, mainly plays the role of breaking the network and providing free oxygen, affecting the precipitation of crystals. 2 The presence of CaO will also increase the expansion coefficient of the glass, resulting in poor thermal stability, making annealing difficult, and inhibiting the precipitation of crystals. CaO can effectively reduce the high-temperature viscosity of the glass and improve the material properties, but the introduction of CaO can easily lead to devitrification of the glass, affect the optical properties of the glass, and reduce the strength of the glass. Therefore, K is not introduced in the present invention. 2 O、Na 2 O, CaO.
[0019] Doping the glass component with an appropriate amount of Nd 2 O 3 and CeO 2 It can effectively inhibit the transformation of the crystal phase of microcrystalline glass from quartz solid solution to spodumene and improve the optical properties of glass. 2 O 3 and CeO 2 Too high content, Nd 2 O 3When the content is >0.3%, the glass will be purple-red. 2 When the content is >0.3%, the glass will turn yellow, thus reducing the transmittance of the glass. 2 O 3 and CeO 2 Under the pinning effect of Nd, the size of the precipitated grains after crystallization can be effectively controlled to improve the transmittance of the glass. Therefore, in the present invention, the Nd content in the base glass is controlled. 2 O 3 and CeO 2 The total content of is below 0.35%, and the amount of each introduced does not exceed 0.3%.
[0020] During the glass melting process, a large amount of gas will be released due to the decomposition and volatilization of the components of the batch. In order to obtain high-quality glass liquid, a certain amount of SnO is added to the glass. 2 As a clarifier to promote the removal of bubbles in the glass liquid, the preferred composition of the present invention is SnO 2 The content is less than 1%.
[0021] Furthermore, the heat treatment process adopted for the melted base glass includes nucleation treatment and crystallization treatment.
[0022] The reaction conditions of the nucleation treatment are: temperature 730-780°C, duration 5-6h.
[0023] The reaction conditions of the crystallization treatment are: 810-890°C, and the duration is 0.5-1h.
[0024] Furthermore, the nucleation treatment adopts a step-by-step nucleation method, including the following steps: heating from room temperature at a rate of 2°C / min to 3°C / min, and when the temperature reaches the glass transition point, keeping it warm for 3 hours to 5 hours; then heating at a rate of 2°C / min to 3°C / min until the temperature reaches 730 to 780°C, and keeping it warm for 5 hours to 6 hours; the nucleation step is completed.
[0025] Furthermore, the crystallization treatment specifically includes the following steps: after the nucleation treatment is completed, the temperature is raised from 730-780°C to 810-890°C at a rate of 2°C / min, and the temperature is kept for 0.5-1h. After the temperature is kept, the temperature is lowered to room temperature at a rate of 0.5°C / min.
[0026] The main crystalline phase of low expansion transparent glass-ceramics is a eutectic of β-quartz and β-spodumene, and the grain size is 20 to 70 nm. When the grain size is greater than 70 nm, the transmittance will decrease.
[0027] The T of the glass-ceramic vis (1mm)≥88%, microhardness>750HV, three-point bending strength>200MPa.
[0028] The base glass is 45×10 -7 / ℃<α (20~400℃) <55×10 -7 / ℃, the expansion coefficient of the crystallized glass can be adjusted within a certain range, α (20~400℃) At -0.3×10 -7 / ℃ and 0.4×10 -7 / ℃.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The microcrystalline glass prepared by the method of the present invention has high permeability, chemical stability and excellent mechanical properties on the basis of low expansion coefficient. It is not only suitable for working environment at room temperature, but also has the characteristic that its use is not affected by high temperature difference.
[0031] (2) Expansion coefficient α of the glass-ceramics prepared by the present invention (20~400℃) At -0.3*10 -7 and 0.4*10 -7 The glass transmittance is greater than T vis (1mm)≥88%, microhardness>750HV, three-point bending strength>200MPa.
[0032] (3) The present invention uses CeO 2 +SnO 2 It acts as a clarifier in the glass melting process and has a composite clarification effect. It is non-toxic and an environmentally friendly clarifier. It also plays a certain pinning role on the grains during the heat treatment process to avoid disordered growth and control the grain size to 20 to 70 nm.
[0033] (4) Compared with the existing microcrystalline glass process, the process of the present invention is not only more environmentally friendly, but also the product produced has good mechanical properties. DETAILED DESCRIPTION
[0034] In order to better understand the technical content of the present invention, specific examples are provided below to further illustrate the present invention. Unless otherwise specified, the experimental methods used in the examples of the present invention are conventional methods in the art.
[0035] The present invention generates microcrystalline glass with specific proportions and specific crystal phases through continuous experiments and research and through crystallization process control, thereby obtaining a low-expansion microcrystalline glass material with high transmittance and high strength.
[0036] In the present invention, unless otherwise specified, the content of each component is expressed in terms of weight percentage of oxides. The glass that has not been crystallized is called basic glass, and the glass that has been crystallized is called microcrystalline glass.
[0037] The main crystal phase of the microcrystalline glass of the present invention is a eutectic body of beta-quartz and beta-spodumene, and the grain size is 20-70nm.
[0038] The present invention provides a heat treatment process for improving the transmittance of low expansion glass-ceramics, which is applied to prepare transparent glass-ceramics with a low expansion coefficient, and comprises the following steps:
[0039] The material prescription is calculated according to the weight percentage in Table 1, and the raw materials are weighed and mixed to obtain a basic batch material. The basic material is heated to 1550-1650° C. in a platinum-rhodium crucible and kept warm for 3 h to 6 h to obtain a glass melt, which is poured onto a preheated mold and annealed in an annealing furnace at 600-700° C.;
[0040] The annealed glass sheet is then placed in a high temperature furnace for heat treatment, and after the heat treatment, a low expansion coefficient transparent microcrystalline glass is obtained. The performance parameters of the low expansion coefficient transparent microcrystalline glass are shown in Table 2.
[0041] The heat treatment includes a nucleation process and a crystallization process:
[0042] The conditions of the nucleation process are: temperature 730-780°C, and heat preservation for 5-6 hours.
[0043] The conditions of the crystallization process are: temperature 810-890°C and holding time 0.5-1h.
[0044] The nucleation process includes the following steps: heating from room temperature at 2°C / min to 3°C / min, and when the temperature reaches the glass transition point, keeping the temperature for 3 to 5 hours; then heating at 2°C / min to 3°C / min until the temperature reaches 730 to 780°C, and keeping the temperature for 5 to 6 hours; the nucleation step is completed.
[0045] Furthermore, the crystallization process comprises the following steps:
[0046] After the nucleation step is completed, the temperature is raised from 730-780°C to 810-890°C at 2°C / min, and the holding time is 0.5-1h. After the holding time is completed, the temperature is lowered to room temperature at 0.5°C / min to complete the heat treatment.
[0047] Through the step-by-step heat treatment method, the grains can grow evenly, avoiding excessive growth and disordered growth, and the grain size is controlled between 20 and 70 nm. The internal stress and thermal deformation of the glass are reduced. Experiments have shown that the linear expansion coefficient of the treated microcrystalline glass can be adjusted within a certain range, α (20~400℃) At -0.3×10 -7 / ℃ and 0.4×10 -7 / ℃, the visible light transmittance increases, the T vis(1mm)≥88%, microhardness>750HV, three-point bending strength>200MPa.
[0048] The following tables respectively provide implementation instructions for low expansion transparent glass-ceramics components and performance parameters of heat-treated glass-ceramics:
[0049] Table 1: Glass composition
[0050]
[0051]
[0052] Table 2: Performance parameters of glass-ceramics after heat treatment
[0053]
[0054] It can be seen from the transmittance of the above examples that the heat treatment process of the present invention can precipitate nano-scale crystal nuclei, the grain size is controlled at 20-70nm, and the expansion coefficient of the microcrystalline glass can be adjusted within a certain range, α (20~400℃) At -0.3×10 -7 / ℃ and 0.4×10 -7 / ℃, and the T vis (1mm)≥88%, the microhardness of the crystallized glass is greater than 750HV, and the three-point bending strength is greater than 200MPa, that is, a transparent crystallized glass with high strength and low expansion is obtained.
[0055] Comparison Example
[0056] Invention patent CN101538118A discloses a method for preparing ultra-low expansion glass-ceramics for laser gyroscopes, wherein the glass-ceramics components include Na 2 O: 0-1%, K 2 O: 0-1%, Sb 2 O 3 / As 2 O 3 :0.5-1.5%. Among them, Na in glass 2 O.K 2 O can play a role in fluxing, but it will reduce the chemical stability of the glass, reduce the hardness and strength of the glass, Sb 2 O 3 / As 2 O 3 The fluxing effect is better, and it was a commonly used clarifier in glass melting in the past, but Sb 2 O 3 / As 2 O 3 All are highly toxic, especially As 2 O 3, the use of this substance is currently strictly prohibited in China.
[0057] Compared with the above-mentioned microcrystalline glass, the present invention does not contain the above components and has good mechanical properties. The microcrystalline glass of the present invention has a microhardness of >750HV and a three-point bending strength of >200MPa after crystallization. 2 +SnO 2 It acts as a clarifier in the glass melting process and has a composite clarification effect. It is non-toxic and an environmentally friendly clarifier. It also plays a certain pinning role on the grains during the heat treatment process to avoid disordered growth and control the grain size to 20 to 70 nm.
[0058] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing transparent microcrystalline glass with a low expansion coefficient, characterized in that: In terms of mass percentage, the raw material composition of the microcrystalline glass is as follows: 60%-75% SiO2, 15%-28% Al2O3, 0.5%-2% TiO2, 2%-5% ZrO2, 2%-8% Li2O, 0%-1% MgO, CeO2+SnO2+P2O5+Nd2O3+ZnO totaling 1%-4%, wherein (TiO2+P2O5+ZrO2) / Li2O is 0.3-1.2, and (MgO+ZnO) / (SiO2+Al2O3)<0.02; The preparation method of the microcrystalline glass comprises the following steps: mixing the raw materials, melting them, and then performing heat treatment, wherein the heat treatment includes nucleation treatment first and crystallization treatment second; the conditions of the nucleation treatment are: temperature of 730-780° C., heat preservation for 5-6 hours; the conditions of the crystallization treatment are: temperature of 810-890° C., heat preservation time of 0.5-1 hour; The nucleation treatment specifically comprises the following steps: heating from room temperature at 2°C / min to 3°C / min, and when the temperature reaches the glass transition point, keeping the temperature for 3 to 5 hours; then heating at 2°C / min to 3°C / min until the temperature reaches 730 to 780°C, and keeping the temperature for 5 to 6 hours; The crystallization treatment specifically includes the following steps: after the nucleation treatment is completed, starting from 730-780°C, heating at 2°C / min to 810-890°C, and keeping the temperature for 0.5-1h; After the insulation was completed, the temperature was lowered to room temperature at 0.5°C / min.
2. A low expansion coefficient transparent microcrystalline glass, characterized in that: Prepared by the preparation method of claim 1.
3. The low expansion transparent glass-ceramics according to claim 2, characterized in that: The expansion coefficient α of the glass-ceramics (20~400℃) At -0.3×10 -7 / ℃ and 0.4×10 -7 / ℃ range.
4. The low expansion transparent glass-ceramics according to claim 2, characterized in that: The glass transmittance of the microcrystalline glass is greater than T vis (1mm) ≥88%, microhardness>750HV, three-point bending strength>200MPa.
Citation Information
Patent Citations
Ultra-low-expansion glass ceramic for laser gyro and preparation method thereof
CN101538118A
Microcrystalline glassware and preparation method thereof
CN112047633A